Tourism and its Role in Environmental Conservation - K.C., Anup (Journal of Tourism and Hospitality Education, 2018)
Ecotourism is a form of tourism which supports biodiversity conservation, socio-cultural development and economic enhancement of a country. It had positive as well as negative impacts on environmental, social and economic aspects of the environment. In the context of Nepal, ecotourism had supported conservation of flora and fauna, livelihood of poor and needy people and development of culture and society. Researchers have used direct observation, questionnaire surveys, focus group discussions and key informant interviews to collect the primary data and different published documents, journals and books for collecting secondary data on ecotourism issues. Also, they have used different analytical techniques based on tabular representation, graphical presentations and statistical methods. Ecotourism had helped to increase the source of revenue which in turn had supported environmental conservation activities. In many areas of the world, floral and faunal diversity had increased significantly by the initiation of ecotourism programs. Dependent people on natural resources, park beneficiaries and park conservators are directly supplemented by the earning received from the ecotourism activities. It has led to disappearance of respect, culture and traditions in some cases while it had also encouraged showing their costumes, songs, dances and other social features in other cases. For long term development of ecotourism, small scale tourism based on community should be focused rather than a large scale mass tourism. Journal of Tourism and Hospitality Education 8 (2018) , Page: 30-47